New processing alternatives for production of low fat and ash sorghum flour - Iva, Florin I. (Kansas State University, 2012)
Sorghum grain is underutilized in the United States. Most sorghum flour available in the market place is whole grain flour with inferior stability and baking characteristics. The demand exists for high quality stable sorghum flour with low fiber and fat content. However, the current decortication step used for separating the bran from endosperm in sorghum milling is not economically viable and the alternatives techniques, which are based on abrasion and frictions, do poor jobs and tend to increase endosperm loss. The lack of information regarding sorghum dry milling to obtain low fat and low ash white sorghum flour is the rationale for developing a suitable flow. Previous research works in this field made some progress towards the achievement of that goal, but not enough to meet the need for high quality white sorghum flour. The main method (named F20105) developed in this study for processing sorghum (without decortication) consists of the following systems: prebreak, a gradual reduction system with purification, and an impact technology. Also, two short laboratory methods were designed for obtaining white sorghum flour for comparison purposes. These were named F20106 and F20107. The method F20106 was based on the use of Buhler Experimental Mill, a Great Western Gyratory Sieve, and Quadrumat Brabender Sr. Experimental Mill. The method F20107 was based on processing decorticated sorghum in a process which uses a hammer mill, a Great Western Gyratory Sieve and an Alpine Pin Mill. A commercial flour was evaluated along with the flours from the different methods in order to make comparisons among them. The long reduction system (FS20105) which included impact detaching techniques produced white sorghum flour with high extraction rate and good baking properties. An impact dehulling machine and a prebreak roller mill were effective in collecting glumes and cracking the sorghum kernels before first break. The shattering effect of the fragile sorghum bran was avoided by implementing air separation of bran from endosperm before each break. A purification system effectively cleaned and sorted the sorghum grits by size. Sorghum flours with different protein contents were evaluated for their baking quality properties. The protein content of sorghum flour was found strongly positive correlated with the amount of water added to the batter, cell wall thickness, cell diameter and cell volume ([rho]>0.85; P<0.0001), and strongly negative correlated with the number of cells/cm2 and L-value of the bread crust (-0.95>[rho]>-0.91; P<0.0001). It was also correlated with the a-value and b-value of the bread crust ([rho]=0.620, P< 0.014 and [rho]=0.520, P< 0.047, respectively). The diagrams F20105, F20106, and F20107 can be used successfully in their current form or with small adjustments to obtain flour from different sorghum hybrids at the laboratory scale. These diagrams also fill a gap in the currently available milling literature. Additionally they can be scaled up in the sorghum processing industry. The growing gluten-free food product market would potentially provide a rapid return on the necessary investment.
Keywords: Sorghum; Milling; Flour; Food Science (0359)